2013
DOI: 10.1097/dcr.0b013e3182a2303e
|View full text |Cite
|
Sign up to set email alerts
|

Local Excision After Preoperative Chemoradiotherapy for Rectal Cancer

Abstract: Our data suggest that local excision is a good option for patients with a major clinical response after chemoradiotherapy. A longer period of follow-up is required to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
114
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(123 citation statements)
references
References 35 publications
6
114
1
2
Order By: Relevance
“…As far as we know, no other study to date has analyzed the effects of treatment interval in a select group of ET patients. The observed overall pCR rate in ET patients in the current study was 16.1 %, which is substantially lower than reported pCR rates in recent literature of 22–44 % 6,8,9,11,30. Several issues for this discrepancy can be noted.…”
Section: Discussioncontrasting
confidence: 81%
“…As far as we know, no other study to date has analyzed the effects of treatment interval in a select group of ET patients. The observed overall pCR rate in ET patients in the current study was 16.1 %, which is substantially lower than reported pCR rates in recent literature of 22–44 % 6,8,9,11,30. Several issues for this discrepancy can be noted.…”
Section: Discussioncontrasting
confidence: 81%
“…Based on large series, it appears that for T3 cancers, 6 to 9 % of LE are performed after CRT [15,16]. This has to be interpreted cautiously as inclusion of ypT0-T1 cancers may significantly increase the LE rate [37,38]. Long-term adverse effects of preoperative radiotherapy should not be underestimated including difficulty in rectal evacuation, incontinence, erectile dysfunction and proctitis [39,40].…”
Section: Limitationsmentioning
confidence: 96%
“…In view of the aforementioned limitations, even if surgical complications, including suture dehiscence and endoanal pain, are not uncommon among patients undergoing LE after CRT, as previously reported by us and others,18,43 this remains a procedure of investigational interest to confirm potential ypT0 status of patients with a major clinical response. On the other hand, a more conservative approach such as the “wait and see” option might be considered for patients with a complete clinical response 44.…”
Section: Discussionmentioning
confidence: 82%
“…In their study, ypT0 was noted in 22 % of the cases, and the 5-year LRFS and DMFS were respectively 100 and 96 %. Similarly, Pucciarelli et al18 reported that the 3-year LRFS was 96.9 % for 43 cT3 or low-lying cT2 rectal cancer patients treated with CRT followed by LE and observation for the ypT0-1 patients.…”
Section: Discussionmentioning
confidence: 89%